Silicon-carbon composite material and preparation method thereof, negative plate, electrochemical device and electronic equipment
By using silicon-carbon composite materials in lithium-ion batteries and using a combined structure of graphite carrier, metal particles and silicon particles, the problems of poor conductivity and volume expansion of silicon negative electrode materials are solved, and the fast charging and cycling performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202310833000.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-07
AI Technical Summary
Silicon anode material has poor fast charging and cycling performance due to poor conductivity and volume expansion in lithium-ion batteries. Existing solutions such as conductive cladding and nano-sized secondary granulation have problems of manufacturing complexity and high cost.
Using silicon-carbon composite materials, metal particles are generated on the graphite carrier and silicon particles and carbon cladding are formed on the surface of their surface. The metal particles are distributed on the surface of the graphite carrier, silicon particles are covered on the surface of the metal particles, and carbon cladding is covered on the surface of the carbon cladding is covered. Silicon particles, the gap filled between the silicon particles, contacts the graphite carrier, and form a silicon-carbon composite material.
The fast charging and circulation performance of lithium-ion batteries have been improved. The lithium-ion window at 4C ratio can reach more than 35% SOC, the number of cycles of 80% SOH can reach more than 830 turns, and the volume expansion rate is low.
Smart Images

Figure CN119275249A_ABST
Abstract
Description
Technical Field
[0001] The present invention specifically relates to a silicon-carbon composite material and a preparation method thereof, a negative electrode sheet, an electrochemical device and an electronic device. Background Art
[0002] With the rapid development of new energy vehicles, drones, mobile robots and other fields, people have put forward more demands for lithium-ion batteries with higher energy density and greater power density. However, for the current mainstream negative electrode material graphite, its fast charging performance is difficult to meet the existing needs. Silicon negative electrode material is considered to be one of the most ideal negative electrode materials for lithium-ion batteries due to its high theoretical specific capacity, low lithium insertion platform voltage and abundant reserves. By combining graphite with silicon, the introduction of silicon can reduce the CW (load mass per unit area of the pole piece) at the pole piece level, thereby helping to improve the fast charging performance. However, the volume of silicon negative electrode materials expands greatly during the cycle, causing the electrode to rapidly decay in capacity during long cycles. In addition, as a semiconductor material, silicon has a very low intrinsic conductivity. The above defects greatly limit the fast charging performance of silicon materials when used in lithium-ion batteries.
[0003] At present, the most commonly used solution to the above defects of silicon materials is to introduce a conductive coating layer. However, since the ion transmission distance of silicon is still large, the improvement effect is limited. Another way is to perform nano-secondary granulation. However, this method has the problems of complex manufacturing process and high cost. Summary of the invention
[0004] In order to overcome the defects of poor conductivity and volume expansion of silicon materials in the prior art, which affect the fast charging and cycle performance of the battery when used as the negative electrode of the battery, the present invention provides a silicon-carbon composite material and a preparation method thereof, a negative electrode sheet, an electrochemical device and an electronic device. The silicon-carbon negative electrode material provided by the present invention has good conductivity and can effectively improve the fast charging performance and cycle performance of the battery.
[0005] In a first aspect, the present invention provides a silicon-carbon composite material, which comprises a graphite carrier, metal particles, silicon particles and a carbon coating layer, wherein the metal particles are distributed on the surface of the graphite carrier; the silicon particles are coated on the surface of the metal particles; the carbon coating layer covers the surface of the silicon particles and fills the gaps between the silicon particles and contacts the surface of the graphite carrier;
[0006] Wherein, based on the total mass of the silicon-carbon composite material, the mass content of the metal particles is 0.01-10wt.%; the mass content of the silicon particles is 0.2wt%-30wt%;
[0007] Wherein, the particle size of the silicon particles is 1-1000nm.
[0008] In a second aspect, the present invention provides a method for preparing a silicon-carbon composite material, comprising the following steps:
[0009] (1) subjecting a mixed solution of a graphite carrier, a metal salt, a reducing agent and a solvent to a first reaction to generate metal particles on the surface of the graphite carrier to obtain a product 1; the mass ratio of the graphite carrier to the metal salt is (1000-10):1;
[0010] (2) subjecting the product 1 to a second reaction with a silicon source to form silicon particles on the surface of the metal particles, thereby obtaining a product 2; the mass content of the silicon particles is 0.2wt%-30wt%; and the particle size of the silicon particles is 1-1000nm;
[0011] (3) Carbon coating the product 2 to form a carbon coating layer, thereby obtaining the silicon-carbon composite material.
[0012] In a third aspect, the present invention provides a silicon-carbon composite material prepared by the preparation method as described above.
[0013] In a fourth aspect, the present invention provides a negative electrode sheet comprising the silicon-carbon composite material as described above.
[0014] In a fifth aspect, the present invention provides an electrochemical device comprising the negative electrode sheet as described above.
[0015] In a sixth aspect, the present invention provides an electronic device comprising the electrochemical device as described above.
[0016] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0017] The reagents and raw materials used in the present invention are commercially available.
[0018] The positive and progressive effects of the present invention are:
[0019] The silicon-carbon composite material provided by the present invention has good electrical conductivity and low volume expansion. When it is applied to the negative electrode material of a lithium-ion battery, the lithium precipitation window at a 4C rate can be above 35% SOC, and the number of cycles at 80% SOH can reach more than 830 cycles, which can effectively improve the fast charging performance and cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Schematic diagram of the structure of the silicon-carbon composite material of the present invention (wherein 1 is a graphite carrier; 2 is a silicon particle; 3 is a carbon coating layer; and 4 is a metal particle).
[0021] Figure 2 The graph is a cycle performance effect diagram of the silicon-carbon composite materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0022] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0023] Silicon Carbon Composite Materials
[0024] In the silicon-carbon composite material provided in the first aspect of the present invention, it comprises a graphite carrier, metal particles, silicon particles and a carbon coating layer, wherein the metal particles are distributed on the surface of the graphite carrier; the silicon particles are coated on the surface of the metal particles; the carbon coating layer covers the surface of the silicon particles and fills the gaps between the silicon particles and contacts the surface of the graphite carrier;
[0025] Wherein, based on the total mass of the silicon-carbon composite material, the mass content of the metal particles is 0.01-10wt.%; the mass content of the silicon particles is 0.2wt%-30wt%;
[0026] Wherein, the particle size of the silicon particles is 1-1000nm.
[0027] In the present invention, the mass content of the metal particles can be obtained by ICP detection; the particle size of the silicon particles is measured by SEM characterization after cross-section polishing (CP) of the material.
[0028] In the present invention, the particle size of the silicon particles refers to the particle size of silicon and metal as a whole. Since the particle size of the metal particles is very small and can be ignored, the whole is the particle size of the silicon particles.
[0029] In the present invention, based on the total mass of the silicon-carbon composite material, the mass content of the metal particles can be 0.01-7.1wt.%, preferably 0.1wt.%-5wt.%; for example, 0.1wt.% or 7.1wt.%, the metal particles quickly grow and etch the graphite carrier and form sub-nano particles, which can be used as sites for silicon deposition and growth, and can control the size of the silicon domain of silicon growth. When the mass content of the metal particles is less than 0.01wt.%, the content is too little, the metal nanocrystals are too little, the deposition size of silicon is too large, and the uniformity is too poor; when the mass content of the metal particles is greater than 10%, it will lead to a low content of active substances, which is not conducive to the improvement of gram capacity.
[0030] In the present invention, the metal particles may be one or more of Pd particles, Pt particles, Ni particles, Rh particles, Fe particles, Cu particles, Co particles, W particles, Cr particles, Ta particles, Mo particles, Mg particles, Sn particles and Ge particles. The metal particles are randomly and discontinuously distributed on the surface of the graphite carrier to facilitate the subsequent formation of discontinuous "silicon islands".
[0031] In the present invention, the particle size of the silicon particles can be 1-150nm, preferably 1-50nm. The size of the silicon particles on the surface can be detected by SEM and CP. When the particle size of the silicon particles is greater than 1000nm, the particle size is too large, which is not conducive to circulation and diffusion of lithium ions; when the particle size of the silicon particles is less than 1nm, it is almost difficult to control the growth.
[0032] In some specific embodiments, the particle size of the silicon particles is 3 nm or 153 nm.
[0033] In the present invention, based on the total mass of the silicon-carbon composite material, the mass content of the silicon particles is 5-20wt.%, for example, 5wt.% or 15wt.%. The silicon content can be analyzed and controlled by TG detection. When the silicon content is greater than 30wt.%, the ion dynamics and structural stability of the silicon-carbon composite material will deteriorate; when the silicon content is less than 0.2wt.%, the dynamics of the structural material cannot be exhibited.
[0034] Preparation method of silicon-carbon composite material
[0035] In the preparation method of the silicon-carbon composite material provided in the second aspect of the present invention, it comprises the following steps:
[0036] (1) subjecting a mixed solution of a graphite carrier, a metal salt, a reducing agent and a solvent to a first reaction to generate metal particles on the surface of the graphite carrier to obtain a product 1; the mass ratio of the graphite carrier to the metal salt is (1000-10):1;
[0037] (2) subjecting the product 1 to a second reaction with a silicon source to form silicon particles on the surface of the metal particles, thereby obtaining a product 2; the mass content of the silicon particles is 0.2wt%-30wt%; and the particle size of the silicon particles is 1-1000nm;
[0038] (3) Carbon coating the product 2 to form a carbon coating layer, thereby obtaining the silicon-carbon composite material.
[0039] In step (1), the metal salt may be a soluble salt that is conventional in the art and can provide a metal element; generally, it is a nitrate and / or sulfate of a metal.
[0040] In step (1), the metal salt is first reduced to a metal element on the surface of the graphite carrier. As the reduction reaction continues, the metal particles gradually grow outward and also etch the graphite carrier inward, thereby embedding into the surface of the graphite carrier and presenting an irregular and discontinuous distribution on the surface of the graphite carrier.
[0041] In step (1), the reducing agent can be a substance conventional in the art that has reducing properties and can reduce the metal salt to a metal element, preferably a metal element, such as Fe and / or Mg.
[0042] In some specific embodiments, the reducing agent is added in the form of an aqueous solution, and the concentration of the reducing agent in the aqueous solution is preferably 1M-10M, such as 5M.
[0043] In step (1), the solvent can be a substance conventional in the art that can provide a reaction environment for the metal salt and the reducing agent, such as water.
[0044] In step (1), the graphite carrier may be graphite conventionally used in the art, such as artificial graphite and / or natural graphite.
[0045] In step (1), the mass ratio of the graphite carrier to the metal salt may be (1000-10):1, preferably (500-10):1, for example 50:1.
[0046] In step (1), the molar ratio of the reducing agent to the metal salt may be (0.1-10):1, for example, 2:3.
[0047] In step (1), the mass ratio of the reducing agent to the solvent may be (0.01-10):1.
[0048] In a specific embodiment, the graphite carrier is preferably also pre-treated, the purpose of the pre-treatment is to activate the surface of the graphite carrier, which is conducive to the growth of metal particles. The pre-treatment method is preferably to activate the graphite carrier in an alkaline solution;
[0049] Wherein, the alkaline solution may be a KOH aqueous solution, and the concentration of KOH in the pretreatment raw material system may be 1M.
[0050] In step (1), the first reaction is preferably carried out in a solution; wherein the temperature of the first reaction is 25-200°C, preferably 60-150°C, for example 180°C; the first reaction is carried out under hydrothermal conditions; and the time of the first reaction is preferably 48h.
[0051] In the present invention, the product 1 is a material formed by the metal particles being distributed on the surface of a graphite carrier.
[0052] In step (2), the silicon source may be conventional in the art, including one or more of silicon dichloride, silicon trichloride and silane; in the present invention, the presence of silicon element may be controlled by selecting the silicon source.
[0053] In step (2), the second reaction is carried out in a solution; the solvent of the solution is preferably ethanol.
[0054] In step (2), the temperature of the second reaction can be a conventional temperature for such reactions in the art, preferably 25-110°C, such as 95°C.
[0055] In step (2), the second reaction can be carried out by a liquid phase method, preferably a hydrolysis method, which can be specifically as follows: product 1, a silicon source and a solvent are placed in a reaction container at the same time, and a hydrolysis reaction and cracking occur in an argon atmosphere at 25-110°C, so that the silicon particles can be coated on the surface of the metal particles.
[0056] In step (2), after the second reaction is completed, preferably a post-treatment is further performed, and the post-treatment step includes acid washing, water washing and drying the reaction product in sequence.
[0057] Wherein, the pickling is preferably carried out using hydrochloric acid.
[0058] Wherein, the water washing is preferably carried out with deionized water.
[0059] Wherein, the drying temperature may be 80°C.
[0060] Wherein, the drying time can be 48 hours.
[0061] In the present invention, the product 2 is a material formed by silicon particles covering the metal particles in the product 1.
[0062] In step (3), the carbon-coated raw material can be conventional in the art, preferably one or more of methane, acetylene and ethylene.
[0063] In step (3), the carbon coating temperature may be 500-1000°C, for example 850°C.
[0064] In step (3), the carbon coating method may be a method conventionally used in the art, preferably a vapor deposition method.
[0065] Negative plate
[0066] A fourth aspect of the present invention provides a negative electrode sheet comprising the silicon-carbon composite material as described above.
[0067] In the present invention, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector. The negative electrode active material layer comprises the silicon-carbon composite material, a conductive agent and a binder as described above.
[0068] The conductive agent is a reagent used to ensure that the electrode has good charge and discharge performance. It can be selected from graphite materials such as natural graphite and artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and other carbon black materials, carbon fibers, metal fibers and other conductive fibers, metal powders such as carbon fluoride powder, aluminum powder, nickel powder and other metal powders, zinc oxide, potassium titanate and other conductive whiskers, and titanium dioxide and other conductive metal oxides or polyphenylene derivatives.
[0069] The binder is a component that helps the active material to bind to the conductive agent and helps the active material to bind to the current collector. It can usually be selected from polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber and various copolymers.
[0070] Among them, the cathode current collector is a substrate supporting the electrode active material, usually a metal foil with a thickness of 3-500 microns. There is no particular restriction on the material, as long as it has high conductivity and does not produce chemical reactions in the secondary battery system. For example, it can be a foil formed after surface treatment of nickel, titanium, aluminum, nickel, silver, stainless steel, carbon, etc. The negative electrode current collector usually has a smooth surface, but fine lines can also be formed on its surface to increase the adhesion between the positive electrode active material and the current collector. In addition to the foil, the negative electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric.
[0071] Electrochemical Devices
[0072] A fifth aspect of the present invention provides an electrochemical device, which comprises the negative electrode sheet as described above.
[0073] In the present invention, the electrochemical device is preferably a battery, and the battery comprises the negative electrode sheet, the positive electrode sheet, the separator and the electrolyte as described above.
[0074] In the present invention, the negative electrode sheet is the same as described above, so its detailed description will be omitted, and only the remaining components will be described in detail.
[0075] Positive electrode
[0076] The positive electrode sheet generally comprises a positive electrode current collector and a positive electrode active material layer formed on one or both sides of the positive electrode current collector. The positive electrode active material layer comprises a positive electrode active substance and optional conductive agent and binder. The added amount can be adjusted within 1-50% of the total amount of the positive electrode active material according to different needs.
[0077] The positive electrode active material may be a material commonly used in the art, including but not limited to one or more of lithium iron phosphate, lithium iron manganese phosphate, ternary positive electrode materials and lithium-rich manganese-based materials.
[0078] The conductive agent is a reagent used to ensure that the electrode has good charge and discharge performance. It can be selected from graphite materials such as natural graphite and artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and other carbon black materials, carbon fibers, metal fibers and other conductive fibers, metal powders such as carbon fluoride powder, aluminum powder, nickel powder and other metal powders, zinc oxide, potassium titanate and other conductive whiskers, and titanium dioxide and other conductive metal oxides or polyphenylene derivatives.
[0079] The binder is a component that helps the active material to bind to the conductive agent and helps the active material to bind to the current collector. It can usually be selected from polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber and various copolymers.
[0080] Among them, the positive electrode current collector is a substrate supporting the electrode active material, usually a metal foil with a thickness of 3-500 microns. There is no particular restriction on the material, as long as it has high conductivity and does not produce chemical reactions in the secondary battery system. For example, it can be a foil formed after surface treatment of nickel, titanium, aluminum, nickel, silver, stainless steel, carbon, etc. The positive electrode current collector usually has a smooth surface, but fine lines can also be formed on its surface to increase the adhesion between the positive electrode active material and the current collector. In addition to the foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric.
[0081] Diaphragm
[0082] The separator provided between the positive electrode sheet and the negative electrode sheet uses an insulating film with high ion permeability and high mechanical strength. The separator is typically 9-18 μm thick; 5-300 μm pore size; 180-380 s / 100 mL air permeability; and 30% to 50% porosity. As the separator, a sheet or non-woven fabric made of an olefin polymer such as polypropylene; glass fiber or polyethylene, which has chemical resistance and hydrophobicity, is used.
[0083] Electrolyte
[0084] The electrolyte used in the lithium ion battery prepared as above generally includes a non-aqueous solvent, a lithium salt, and an additive.
[0085] The non-aqueous solvent may be a conventional non-aqueous solvent in the art, preferably an ester solvent, more preferably a carbonate solvent. The carbonate solvent is preferably one or more of ethylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC).
[0086] Among them, the lithium salt may be at least one of LiPF6, LiBF4, LiN(SO2F)2 (abbreviated as LiFSI), LiClO4, LiAsF6, LiB(C2O4)2 (abbreviated as LiBOB), LiBF2(C2O4) (abbreviated as LiDFOB), LiN(SO2RF)2, LiN(SO2F)(SO2RF). Preferably, the content of the lithium salt in the electrolyte is 5-20%.
[0087] The additive is preferably one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), dithiothreitol (DTD), dithiothreitol sulfate, 1,3-propane sultone (PS), propene sultone and 1,4-butane sultone. The conventional amount of the additive in the electrolyte is 1-4% of the electrolyte, for example 2%.
[0088] In the present invention, the battery is generally a square hard-shell battery, a soft-pack battery and a cylindrical battery.
[0089] The battery can be prepared by conventional methods in the art. Generally, the preparation method of the battery includes the following steps: the positive electrode sheet, the negative electrode sheet and the separator are sequentially cut, cut and stacked or wound to form a bare cell, the bare cell is JR-shelled, and the water content is fully baked to be below 450ppm, and the processes of liquid injection, formation, sealing, inspection and the like are completed to prepare a square hard shell.
[0090] Electronic devices
[0091] The electronic device provided in the sixth aspect of the present invention includes the electrochemical device as described above.
[0092] Exemplarily, the electronic device described in the present invention may be, but is not limited to, mobile devices (such as mobile phones, tablet computers, laptop computers, video recorders, portable printers / copiers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems and backup power supplies, etc.
[0093] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0094] Example 1
[0095] (1) Using graphite with a D50 of 1-15 μm as a carrier, the activated graphite carrier is activated by 1M KOH aqueous solution; then the activated graphite carrier is placed in Cu(NO3)2, wherein the mass ratio of the graphite carrier to Cu(NO3)2 is 50:1; Fe and Cu(NO3)2 are added at a molar ratio of 2:3, and reacted under hydrothermal conditions at a reaction temperature of 180°C and a reaction time of 48 hours, so that a layer of metal particles grows on the surface of the graphite carrier, and these metal particles gradually etch the surface of the graphite carrier to serve as active sites for the subsequent growth of silicon particles. The content of the metal particles is controlled at 0.1wt%, which is recorded as product 1;
[0096] (2) Product 1, silicon dichloride and ethanol are placed in a stirring tank, and reacted under the conditions of argon as a protective gas and a reaction temperature of 95°C, and silicon nanoparticles are grown on the surface of Product 1; after the reaction is completed, the product is pickled with hydrochloric acid and washed with deionized water, and then dried at 80°C for 48 hours, and a layer of island-shaped silicon nanoparticles is prepared on the surface of Product 1, and the silicon particle size is 3 nm, which is recorded as Product 2;
[0097] (3) Using methane as a carbon source, a uniform carbon coating layer 3 is deposited and grown on the surface of the product 2 at 850°C by a vapor deposition method, and finally a silicon-carbon composite material is obtained, which is denoted as a graphite@Si@C composite material. The schematic diagram of its structure is shown in FIG. Figure 1 shown.
[0098] Example 2
[0099] The difference from Example 1 is that in step (1), the metal content is controlled at 7.1 wt %, the silicon content is 15 wt %, and the other steps are the same.
[0100] Example 3
[0101] The difference from Example 1 is that in step (2), the silicon particle size is controlled to be 153 nm, and the other steps are the same.
[0102] Comparative Example 1
[0103] The difference from Example 1 is that step (1) is omitted, graphite is used as the substrate, and steps (2) and (3) are directly performed, and the rest are the same.
[0104] Comparative Example 2
[0105] The difference from Example 1 is that in step (1), the metal content is controlled at 15.1 wt %, the silicon mass content is 35 wt %, and the other steps are the same.
[0106] Comparative Example 3
[0107] The difference from Example 1 is that in step (2), the silicon particle size is controlled to be 1528 nm, the silicon mass content is 20 wt %, and the other steps are the same.
[0108] Effect Example
[0109] Preparation of lithium-ion secondary batteries
[0110] (1) Preparation of positive electrode
[0111] The positive electrode material, conductive agent Super P, and binder polyvinylidene fluoride (PVDF) prepared above are mixed in a weight ratio of 97:1.5:1.5, and solvent N-methylpyrrolidone (NMP) is added, and the mixture is fully stirred to obtain a positive electrode slurry; the positive electrode slurry is coated on a positive electrode current collector aluminum foil, and a positive electrode sheet is prepared through processes such as drying, cold pressing, and slitting.
[0112] (2) Preparation of negative electrode sheet
[0113] The silicon-carbon composite material obtained in the embodiment and the comparative example, the conductive agent acetylene black, the thickener CMC, and the binder SBR were mixed in a mass ratio of 96.4:1:1.2:1.4, and deionized water was added as a solvent, and the mixture was fully stirred to obtain a negative electrode slurry; the negative electrode slurry was evenly coated on the negative electrode current collector copper foil, and a positive electrode sheet was prepared through processes such as drying, cold pressing, and slitting.
[0114] (3) Preparation of electrolyte
[0115] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0116] (4) Preparation of diaphragm
[0117] A PE porous membrane with a thickness of 11 μm is used as a separator (wherein the thickness of the separator is 9 μm to 18 μm; the air permeability is 180 s / 100 mL to 380 s / 100 mL; the porosity is 30% to 50%)
[0118] (5) Preparation of lithium-ion secondary batteries
[0119] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in sequence, so that the separator is placed between the positive and negative electrode sheets to play a role of isolation. Then, the aluminum plastic film is wrapped, and after drying, the above-prepared electrolyte is injected. After packaging, standing, formation and other processes, a soft-pack battery (i.e., lithium-ion secondary battery) with a capacity of 1Ah is finally prepared.
[0120] 1. Lithium deposition window test method
[0121] The lithium precipitation window is an important indicator for judging the dynamics of materials. A lithium precipitation window > 80% SOC is the extreme at a 4C rate; a lithium precipitation window < 10% SOC can basically be judged as poor material dynamics. The higher the lithium precipitation window, the better the fast charging performance of the material. The lithium precipitation window of the present invention is preferably 10-80% SOC, particularly preferably 15-50% SOC. (SOC: State of charge; battery charging state)
[0122] The test method is: at 25°C, discharge the battery to 2.5V at 0.33C current, let stand for 1 minute, then charge to 4.25V at 1C, constant voltage to 0.05C, discharge to 2.5V at 0.33C current, let stand for 1 minute; then charge to 4.25V at 2C, constant voltage to 0.05C, discharge to 2.5V at 0.33C current; let stand for 1 minute, then charge to 4.25V at 4C, constant voltage to 0.05C, discharge to 2.5V at 0.33C current.
[0123] 2. Cyclic performance test method
[0124] At 25°C, the battery is cycled at 0.33A / g (calculated based on the mass of the positive electrode material) and 2.5-4.25V. When the battery reaches 80% SOH, the corresponding number of cycles is the cycle performance of the battery. 80% SOH is defined as the battery discharge capacity at this time divided by the discharge capacity of the first cycle, which is 80%, which is the battery cycle performance. (SOH: State of health, battery health status)
[0125] 3. TG test
[0126] Tested according to GB / T 31984-2015.
[0127] 4. ICP test
[0128] Tested to BS EN ISO 14720-2-2013.
[0129] 5. Volume expansion rate
[0130] Volume expansion rate = (pole sheet thickness after 50 cycles - pole sheet thickness before assembly) / (pole sheet thickness before assembly - copper foil thickness) * 100%.
[0131] The testing method for silicon layer thickness and carbon layer thickness is as follows: identify the silicon layer and carbon layer through EDS element distribution, and then test the thickness of the electrode section under a scanning electron microscope, with a test magnification of 100,000 times and a voltage of 15kV.
[0132] Table 1
[0133]
[0134] In this field, the lithium precipitation window is an important indicator for judging the material dynamics. A lithium precipitation window > 80% SOC is already the limit at a 4C rate; when the lithium precipitation window < 10% SOC, it can be basically judged that the material dynamics are poor.
[0135] According to Table 1 and Figure 2 It can be seen from the data that the silicon-carbon composite material provided by the present invention has a lithium precipitation window @4C above 35% SOC, a cycle number at 80% SOH above 830, and a volume expansion rate below 50%.
[0136] In Comparative Example 1, the silicon-carbon composite material does not include metal particles. It can be seen that its lithium precipitation window @4C is 9.8% SOC, indicating that it starts to precipitate lithium when it is charged to 9.8% of the fully charged state under 4C conditions, which seriously limits the fast charging performance of the battery; and the cycle performance is also poor, with only 400 cycles at 80% SOH. This may be due to the rapid growth and etching of metal to form sub-nano particles, which can serve as sites for silicon deposition and growth, and can control the size of silicon domains for silicon growth. When metal particles are not included, silicon lacks active sites for growth, which may cause silicon particles to be continuously distributed on the graphite carrier with poor uniformity.
[0137] In Comparative Example 2, the metal particle content and the mass content of silicon particles are not within the scope of the present invention. It can be seen that the effects of lithium precipitation window, cycle performance and volume expansion rate are far worse than those of the present invention. This may be because when the metal particle content and the mass content of silicon particles are too large, the ion dynamics and structural stability of the silicon-carbon composite material will deteriorate, resulting in poor fast charging performance and large volume expansion.
[0138] In Comparative Example 3, the size of its silicon particles is not within the scope of the present invention. It can be seen that the effects of its lithium precipitation window, cycle performance and volume expansion rate are far worse than those of the present invention. This may be because the size of the silicon particles is too large, which is not conducive to the diffusion of lithium ions, thereby affecting the fast charging performance and cycle performance.
[0139] The above is only a specific embodiment of the present invention. However, the present invention is not limited to the specific details in the above embodiment, and within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, and these simple modifications all belong to the protection scope of the present invention.
[0140] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0141] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A silicon-carbon composite material, characterized in that: It includes a graphite carrier, metal particles, silicon particles and a carbon coating layer, wherein the metal particles are distributed on the surface of the graphite carrier; the silicon particles are covered on the surface of the metal particles; the carbon coating layer covers the surface of the silicon particles and fills the gaps between the silicon particles and contacts the surface of the graphite carrier; Wherein, based on the total mass of the silicon-carbon composite material, the mass content of the metal particles is 0.01-10wt.%; the mass content of the silicon particles is 0.2wt%-30wt%; Wherein, the particle size of the silicon particles is 1-1000nm.
2. The silicon-carbon composite material according to claim 1, characterized in that: The metal particles are distributed discontinuously on the surface of the graphite carrier.
3. The silicon-carbon composite material according to claim 1, characterized in that: The silicon particles satisfy at least one of the following conditions ab: a. The particle size of the silicon particles is 1-150nm; b. Based on the total mass of the silicon-carbon composite material, the mass content of the silicon particles is 5-20wt%.
4. The silicon-carbon composite material according to claim 1, characterized in that: The metal particles satisfy at least one of the following conditions ab: a. The mass content of the metal particles is 0.01-7.1wt.%; b. The metal particles are one or more of Pd particles, Pt particles, Ni particles, Rh particles, Fe particles, Cu particles, Co particles, W particles, Cr particles, Ta particles, Mo particles, Mg particles, Sn particles and Ge particles.
5. A method for preparing a silicon-carbon composite material, characterized in that: It includes the following steps: (1) subjecting a mixed solution of a graphite carrier, a metal salt, a reducing agent and a solvent to a first reaction to generate metal particles on the surface of the graphite carrier to obtain a product 1; the mass ratio of the graphite carrier to the metal salt is (1000-10):1; (2) subjecting the product 1 to a second reaction with a silicon source to form silicon particles on the surface of the metal particles, thereby obtaining a product 2; the mass content of the silicon particles is 0.2wt%-30wt%; and the particle size of the silicon particles is 1-1000nm; (3) Carbon coating the product 2 to form a carbon coating layer, thereby obtaining the silicon-carbon composite material.
6. The method for preparing the silicon-carbon composite material according to claim 5, characterized in that: The method for preparing the silicon-carbon composite material satisfies one or more of the following conditions ae: a. In step (1), the mass ratio of the graphite carrier to the metal salt is (1000-10): 1; b. In step (1), the molar ratio of the reducing agent to the metal salt is (0.1-10): 1; c. In step (1), the mass ratio of the reducing agent to the solvent is (0.01-10): 1; d. In step (1), the temperature of the first reaction is 25°C-200°C; e. In step (2), the temperature of the second reaction is 25°C-110°C.
7. A silicon-carbon composite material, characterized in that: It is prepared by the preparation method described in claim 5 or 6.
8. A negative electrode sheet, characterized in that: It comprises the silicon-carbon composite material as described in any one of claims 1-4 and 7.
9. An electrochemical device, characterized in that: It comprises the negative electrode sheet as claimed in claim 8.
10. An electronic device, characterized in that: It comprises the electrochemical device as claimed in claim 9.
Citation Information
Cited By
Material for lithium battery anode
WO2026165036A1